Height width ratio of frontal sinus in different stages of cervical vertebrae maturation in subjects with normal occlusion - Gayathri Prakash Anand; Ani G, Suja; Peter, Elbe (Journal of Orofacial Research, 2023)
Background & Objectives: The recognition of pubertal growth spurt is an important aspect of Orthodontics. Morphological changes of the frontal sinus during adolescent growth spurt have evoked the interest of many authors. The present study aimed to evaluate the height-width ratio of frontal sinus in different stages of cervical vertebral maturation (CVM) and if possible, to determine the clinical relevance of frontal sinus morphologic variations in assessing the developmental status of an individual. Method: A cross-sectional study was performed on pretreatment lateral cephalograms of 115 subjects aged 7 to 22 years. The sample was divided into six groups based on the cervical vertebral maturation stages and five groups based on chronological age. The height-width ratio of the frontal sinus was calculated and CVM stages were evaluated on the same radiograph. The comparison of height-width ratios with the different CVM stages was done using one-way ANOVA. A pair-wise comparison was done by Duncan’s post-hoc test. Student’s t-test was used for comparison of the frontal sinus parameters with gender. Correlations of the parameters with CVM stages gender-wise were done using Kendall’s tau_b test. Results: Results showed that the height-width ratio of the frontal sinus in the study population does not differ with different age groups or the CVM stages. The height-width ratio failed to show any significant change with age or cervical maturation stages in the sample. Conclusion: The frontal sinus height-width ratio failed to show a specific pattern among the different CVM stages and hence, could not characterize an adolescent growth spurt.